The value of HDL subfractions in predicting cardiovascular outcomes in untreated, diabetic patients with stable coronary artery disease: An age- and gender-matched case-control study - Zhang, Wei; Jin, Jing-Lu; Zhang, Hui-Wen; Zhu, Ya-Xin; Dong, Qian; Sun, Jing; Guo, Yuan-Lin; Dou, Ke-Fei; Xu, Rui-Xia; Li, Jian-Jun (Frontiers in Endocrinology, 2023)
Objective: The aim of the present study was to examine the value of high-density lipoprotein (HDL) subfractions for predicting cardiovascular events (CVEs) in untreated patients with type 2 diabetes mellitus (T2DM) and stable coronary artery disease (SCAD) using an age-and gender matched case-control study. Methods: 185 SCAD patients and 185 T2DM and SCAD patients were enrolled and subjected to a clinical follow-up of CVE. HDL subfractions were analyzed using the Quantimetrix Lipoprint System. The relationship between HDL subfractions and CVEs in patients with T2DM and SCAD was evaluated by Kaplan-Meier analysis and Cox proportional hazard models. Results: During a median of 37.7-month follow-up, patients with T2DM and SCAD had a higher percentage of CVEs (p=0.039). The combined concentrations of intermediate and small HDL-C (defined as the mixed HDL subfractions) were related to the event incidence in patients with T2DM and SCAD (p=0.004) and still positively associated with increased CVEs even after adjustment in 3 models. Kaplan-Meier curve analysis displayed those patients with T2DM and SCAD in higher levels of mixed HDL subfractions group (>28mg/dl) had lower event-free survival rates (p=0.008). Conclusions: Elevated intermediate and small HDL subfractions concentration could predict events in patients with T2DM and SCAD.